Source-reservoir rock assemblages and hydrocarbon accumulation models in the Middle-Lower Jurassic of eastern Sichuan Basin, China - Bai, Rong; Zhang, Shaomin; Hong, Haitao; Qin, Chunyu; Li, Yucong; Cai, Changhong; Kong, Xiangye; Li, Nan; Lei, Dong; Lei, Xin; Wang, Changyong; Jin, Tao; et al. (Frontiers in Earth Science, 2023)
The eastern Sichuan Basin in China holds vast potential for oil and gas exploration in the Lower-Middle Jurassic strata. However, the geological characteristics and hydrocarbon accumulation patterns of this region remain largely unclear. During the deposition period of the Lower-Middle Jurassic strata, the eastern Sichuan is characterized by the formation of multiple sets of source, reservoir, and caprock assemblages through depositing lake-delta-fluvial deposits, which have great exploration potential. The Jurassic source rocks in eastern Sichuan are mainly developed in the Dongyuemiao Member, Da’anzhai Member, and Liangshan Formation. These source rocks have a total organic carbon (TOC) content greater than 1 and a varying range of organic matter maturity, with a Ro value of 0.8 to 2.0. The kerogen in these source rocks is primarily type II, with a smaller proportion being type III. A range of reservoir rocks can be found in the Jurassic strata of eastern Sichuan, with sandstone reservoirs being predominantly found in the Liangshan Formation, Shaximiao Formation, and Zhenzhuchong Member. Shale reservoirs are mostly present in the Dongyuemiao, Da’anzhai, Liangshan, and Maanshan Members, and there is a limited distribution of limestone reservoirs in the Da’anzhai Member and Dongyuemiao Formation. The arrangement of source rocks and reservoir rocks in eastern Sichuan has led to the formation of three types of reservoir-forming combinations, including lower generation and upper storage, self-generation and self-storage, and composite. Sandstone reservoirs are typically of lower generation and upper storage, shale reservoirs are primarily of self-generation and self-storage, and limestone reservoirs are mostly composite. The exploration of Jurassic oil and gas in eastern Sichuan should prioritize "layer and area selections."The degree of fracture development in the exploration area also has a significant impact on the shale oil and gas content. The Liangshan Formation and Shaximiao Formation sandstone reservoirs can serve as secondary exploration targets, with anticline areas that have better sealing conditions being more favorable. Limestone reservoirs have limited distribution, and exploration areas with high and steep fractures are relatively more advantageous.